Analysis of the Factors Affecting Farm-Level Output of Mangoes among Small-Scale Farmers in Machakos County, Kenya - Musyoka, John Kennedy; Isaboke, Hezron Nyarindo; Ndirangu, Samuel Njiri (Machakos University Press, 2021)
The study examined the factors affecting farm-level output of mangoes among small-scale farmers in Machakos County, Kenya. Data was obtained from a sample of 352 small-scale mango farmers that were proportionately selected from six wards of the study area. A structured interview schedule was used for data collection. Both descriptive and inferential statistics were employed in data analysis. The stochastic Cobb-Douglas production function results indicated that active family and hired labour, pesticides, and manure were the inputs that influenced mango output with 0.463 return to scale. This indicates a decreasing return to scale of mango output in the study area. In addition, household size, mango farming income, farm size, amount of credit, and extension contacts were the factors that had a positive effect on mango farm-level output, while cost of pesticides and cost of manure precipitated a negative effect. The study recommends to the Ministry of Agriculture in collaboration with County Government to strengthen the extension contact between farmers and agricultural extension agents by making frequent visits to mango farmers and organizing training programs to encourage them to apply good management practices for improved production. Furthermore, small-scale mango farmers access to functional input markets will enhance farm-level mango output.
Keywords: Mango; Farm-level output; Cobb-Douglas production